SARS-CoV-2 Serology Status Detected by Commercialized Platforms Distinguishes Previous Infection and Vaccination Adaptive Immune Responses. (17th August 2021) - Suhandynata, Raymond T; Bevins, Nicholas J; Tran, Jenny T; Huang, Deli; Hoffman, Melissa A; Lund, Kyle; Kelner, Michael J; McLawhon, Ronald W; Gonias, Steven L; Nemazee, David; Fitzgerald, Robert L
Abstract: Background: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has infected over 110 million individuals and led to 2.5 million deaths worldwide. As more individuals are vaccinated, the clinical performance and utility of SARS-CoV-2 serology platforms needs to be evaluated. Methods: The ability of 4 commercial SARS-CoV-2 serology platforms to detect previous infection or vaccination were evaluated using a cohort of 53 patients who were SARS-CoV-2 PCR positive, 89 SARS-CoV-2-vaccinated healthcare workers (Pfizer or Moderna), and 127 patients who were SARS-CoV-2 negative. Serology results were compared to a cell-based SARS-CoV-2 pseudovirus (PSV) neutralizing antibodies assay. Results: The Roche S-(spike) antibody and Diazyme neutralizing antibodies (NAbs) assays detected adaptive immune response in 100.0% and 90.1% of vaccinated individuals who received 2 doses of vaccine (initial and booster), respectively. The Roche N-(nucleocapsid) antibody assay and Diazyme IgG assay did not detect adaptive immune response in vaccinated individuals. The Diazyme NAbs assay correlated with the PSV SARS-CoV-2 median infective dose (ID50 ) neutralization titers ( R 2  = 0.70), while correlation of the Roche S-antibody assay was weaker ( R 2  = 0.39). Median PSV SARS-CoV-2 ID50 titers more than doubled in vaccinated individuals who received 2 doses of the Moderna vaccine (ID50, 597) compared to individuals who received a single dose (ID50, 284). Conclusions: The Roche S-antibody and Diazyme NAbs assays robustly detected adaptive immune responses in SARS-CoV-2 vaccinated individuals and SARS-CoV-2 infected individuals. The Diazyme NAbs assay strongly correlates with the PSV SARS-CoV-2 NAbs in vaccinated individuals. Understanding the reactivity of commercially available serology platforms is important when distinguishing vaccination response versus natural infection.